Legal Design Thinking untuk Edukasi Konsumen Generasi Z terhadap Risiko Kesehatan Pangan Inovatif di E-Commerce - Ilham Komarudin; Domingos Soares; Agus Santoso, Aris Prio; Retna Dewi Lestari (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to develop a legal education strategy based on Legal Design Thinking to enhance Generation Z's understanding of food safety risks in the e-commerce environment. Employing a qualitative descriptive method with a literature and conceptual approach, the research analyzes the application of Legal Design Thinking in legal education related to innovative food products. The novelty of this study lies in the use of Legal Design Thinking as a visual, participatory, and user-centered legal education strategy, an approach that has not been comprehensively explored in previous research. The findings indicate that this approach can transform legal education into a more inclusive and adaptive model tailored to the digital characteristics of Generation Z. By integrating user empathy, legal visualization, and technological innovation into a problem-based design process, Legal Design Thinking simplifies complex regulations into easily understandable information while promoting active engagement of young people as legal subjects. In the context of e-commerce, this approach bridges the legal communication gap and fosters a culture of consumer protection grounded in collaboration and sustainable digital legal literacy. In conclusion, Legal Design Thinking is a strategic innovation that should be adopted by relevant institutions and educational bodies through cross-disciplinary collaboration and the use of digital media.